Mineral and bulk compositions measured by EPMA, geochronological data measured by LA-ICP-MS and SIMS, for the Wutai-Fuping crustal section - Jia-Hui Liu; Jonas Kaempf; Meiyun Huang; Nicolas Riel; Jinghui Guo; Guangyu Huang; Lin Chen; Shujuan Jiao; Mengxia Mao; Chris Clark; Juan Wang; Qian W L Zhang; et al. (PANGAEA, 2025)
We collected major and minor element microprobe compositions, garnet Lu-Hf geochronology, and zircon U-Pb geochronology data for the metapelites in the Wutai–Fuping crustal sections (GPS 112°59 extquotesingle53 extquotesingle extquotesingleE, 38°56 extquotesingle49 extquotesingle extquotesingleN), Trans-North China Orogen, China. The sample collections and data measurements were performed in 2015-2024, to understand the metamorphic grade, timing, and the tectonic setting of this region. Major and minor element microprobe compositions were measured in rock thin sections using microprobe scanning mapping on a JEOL-8230 electron probe micro-analyzer (EPMA) instrument at the School of Resources and Environmental Engineering, Hefei University of Technology, China in 2023. Then we processed them using XMapTools (doi:10.5281/zenodo.7656958.), and the compositional data for minerals and bulk rocks were extracted from XMapTools. The acquisition of composition helps us to calculate the metamorphic pressure-temperature conditions. In situ garnet Lu-Hf geochronological data was measured using a RESOlution 193 nm excimer laser-ablation (LA) system connected to an Agilent 8900 QQQ ICP-MS at the John de Laeter Centre (JdLC) at Curtin University, Australia in 2024. The garnet Lu-Hf geochronological data helps constrain the peak metamorphic timing of this region. SIMS U-Pb zircon geochronological data. We measured zircon U-Pb isotope using a Cameca IMS-1280 SIMS mass spectrometer at the Institute of Geology and Geophysics, Chinese Academy of Sciences (IGGCAS), Beijing, China in 2024. The zircon data helps constrain the metamorphic timing of this region.